MENINGKATKAN HASIL BELAJAR IPA TENTANG KEANEKARAGAMAN HEWAN DAN TUMBUHAN MELALUI METODE PROBLEM BASED LEARNING - Zulfyansyah, Zulfyansyah (Pascasarjna Universitas Negeri Jakarta, 2015)
Abstract: objective singer to review the findings improve science learning aboutdomesticated animal and plant through project based learning method (project basedlearning) at grade elementary school. research singer using a class action researchmethods according kemmis and mc.taggart that done during cycle prayer. research resultsshow that increase student learning results in science subjects 22 students that amountshearts understanding basic competence explain outer animal body shape and functionwell as plants using project based learning method. it can be evidenced with singer testscore results students learn in cycle 1 ie 50% of students average completed by class 61,increases in cycle 2 reaches 91% of students completed an average with class teacher andstudent activity 84. match step-step method singer reached 100% (masteri learning)conclusion on cycle 2. implementation project-based learning method can be improvelearning results ipa regarding the domesticated animal and plant competency explainaffairs animal body shape and also plants function well as enhance the activity,seriousness and cooperation student learning hearts follow.Keywords: Findings learn science, project based learning method, domesticated animals and plants.